Soil recovery after Cyclone Gabrielle : building back better : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, New Zealand - Dickson, Alexandra (Massey University, 2025)
Cyclone Gabrielle, which struck New Zealand’s North Island in February 2023, caused unprecedented damage to the North Island of New Zealand; the East Coast including Hawke’s Bay, Wairoa and Gisborne were some of the worst affected areas. As a result of the destructive flood waters, a vast amount of sediment was deposited on high-value horticultural and cropping land. In the aftermath, there was limited information available to guide landowners in restoring the productive capacity of this highly productive land (HPL). This research aimed to address knowledge gaps through a combined literature review and field-based study. The initial objective was to understand the geographical and geological setting of Hawke’s Bay and consolidate prior understanding of flood sediment impacts. Baseline soil and sediment data was collected from a range of affected sites shortly after the cyclone, assessing physical, chemical, and biological characteristics. A subset of these sites was revisited twelve months later to evaluate short term changes and management outcomes. Results showed that sediment characteristics varied widely by texture and catchment, with sandy sediments presenting significant physical and fertility challenges. From 2023 to 2024 there was positive outcomes nutrient levels, linked to fertiliser application, and incorporation of sediment into antecedent soil. Soil organic matter levels were consistently low and continued to decline, and earthworm populations remained suppressed. Despite variability in management responses, some growers observed improvements in soil physical properties, particularly where early interventions such as regrassing were employed. This research highlights the importance of rapid dissemination of management advice immediately after a flood, the need for longer-term monitoring to understand medium to long-term impact and recovery, and the value of coordinated knowledge storage for future events. The findings provide practical insights for growers and policymakers and lay the groundwork for further research into the economic and ecological dimensions of flood sediment recovery in high-value vegetable and horticultural systems, on highly productive land.
Keywords: 410405 Environmental rehabilitation and restoration